2006
DOI: 10.1111/j.1743-6109.2006.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Paradigms from a Historical DSM-III and DSM-IV View Toward an Evidence-Based Definition of Premature Ejaculation. Part II—Proposals for DSM-V and ICD-11

Abstract: Background. In the Diagnostic and Statistical Manual of Mental Disorders (DSM), a descriptive definition for premature ejaculation (PE) that was based on historical assumptions has been accepted. Aim. To formulate a new functional definition of PE in the DSM. Methods. A "syndrome" approach instead of a "complaint" approach is applied and evidence-based data from epidemiological and clinical studies are used. Results.A new functional definition of PE should pertain to a cluster of "symptoms" of a distinct "synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
196
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(207 citation statements)
references
References 41 publications
8
196
0
3
Order By: Relevance
“…2,4 However, recent research by Patrick et al 11 has questioned the usefulness of IELT as a primary or sole criterion for diagnosis because of the observed cultural variability. Furthermore, it is known that men will generally overestimate their IELT, 2,3 which also brings into question the validity of IELT in diagnosis when objective measurement is not utilized, although men with very short IELTs do estimate Abbreviations: PE, premature ejaculation; no-PE, no premature ejaculation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,4 However, recent research by Patrick et al 11 has questioned the usefulness of IELT as a primary or sole criterion for diagnosis because of the observed cultural variability. Furthermore, it is known that men will generally overestimate their IELT, 2,3 which also brings into question the validity of IELT in diagnosis when objective measurement is not utilized, although men with very short IELTs do estimate Abbreviations: PE, premature ejaculation; no-PE, no premature ejaculation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that men will generally overestimate their IELT, 2,3 which also brings into question the validity of IELT in diagnosis when objective measurement is not utilized, although men with very short IELTs do estimate Abbreviations: PE, premature ejaculation; no-PE, no premature ejaculation. 2,4 have appropriately questioned the vagueness of terms such as 'minimal', 'before the person wishes' and 'persistent' used in DSM-IV-TR (and earlier DSM versions) in the diagnosis of PE. The PEDT was developed specifically to address this issue, the results of earlier research, 7 and this study, demonstrating that a simple tool can be used to standardize these somewhat vague terms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some international epidemiologic studies demonstrated lower prevalence for PE in Middle East, confirming this presumption (36). However, clinical studies regarding the penile sensitivity, PE status and sexual satisfaction report conflicting results are not conclusive (11,(141)(142)(143)(144)(145).…”
Section: Circumcision and Pementioning
confidence: 72%